Clinical Importance of Vitamins, Cytokines and Mirna Expression among Type II Diabetic Patients - Ashfaq Ahmad, Jawad Ullah, Muhammad Khan Malik, Hina Sadaf, Syed Zamir-Ul-Hassan, Mohsin Shafi, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Nutrigenomic refers to the study of interactions between nutrients and food components with the human genome, evaluating how gene expression and metabolic functions can be affected by feeding. Objective: To find the clinical importance of vitamins, cytokines and miRNA expression among Type II diabetic patients. Study Design: Cross-sectional study Place and Duration of Study: Department of Pathology, Khyber Medical College, Peshawar from 1st January to 30th June 2023. Methodology: Two hundred and twenty patients suffering from type II diabetes were enrolled. The clinical and demographic information was collected for each participant. Relevant variables such as age, gender, duration of diabetes, and measures of glycemic control and HbA1c levels were collected through thorough review of medical records. Fasting venous blood samples were obtained from all study participants to ensure standardization. Results: There is a significant negative correlation between HbA1c and Vitamin D levels (r = -0.25, p<0.01), and a positive correlation between the duration of diabetes and miR-375 (r = 0.30, p<0.05). Diabetic retinopathy was weakly associated with IL-6 (r = 0.22, p=0.04), while diabetic neuropathy had a mild correlation with TNF-α (r = 0.18, p=0.07). Additionally, the study observed a weak inverse correlation between Vitamin C and miR-126 (r = -0.15, p=0.12). Conclusion: Vitamins, cytokines, and miRNA expression profiles in disease pathogenesis offer promising avenues for personalized therapeutic interventions aimed at optimizing metabolic control and reducing the burden of diabetic complications. Emerging evidence suggests that miRNAs are differentially expressed, and indeed have a potential causative role, in diabetes and its related complications. Keywords: Patients, miRNA, T2DM, Vitamins, Cytokines.